Pore structure characterization of kaolin, metakaolin, and their acid-treated products using small-angle X-ray scattering - Vollet, Dimas R. [UNESP]; Macedo, JoséCarlos D.; Mascarenhas, Yvonne P. (Elsevier, 1994)
Pore structure of dealuminated kaolin and metakaolin was studied by small-angle X-ray scattering (SAXS). Both parent kaolin and metakaolin have about 10% of the total pore volume provided by globular pores with 105 Å mean pore size. Their surface area is about 14 m2/g. Acid dealumination of kaolin causes an increase of its globular pore volume without an appreciable change in the mean pore size, its surface area increasing up to about 90 m2/g. Acid dealumination of metakaolin enhances the globular pore volume, although there is generation of slit-shaped pores with a narrow thickness distribution whose mean value is 14 Å. This interlayer spacing causes an increase in surface area of about 190 m2/g by SAXS. © 1994.
Keywords: dealumination; kaolin; pore structure; small angle X-ray scattering; Acids; Characterization; Clay products; Porosity; Surface properties; X ray analysis; Acid dealumination; Acid treatment; Globular pore volume; Metakaolin; Small angle X ray scattering (SAXS); Kaolin